2016
DOI: 10.4088/jcp.15m09936
|View full text |Cite
|
Sign up to set email alerts
|

Doomed for Disorder? High Incidence of Mood and Anxiety Disorders in Offspring of Depressed and Anxious Patients

Abstract: Offspring of depressed and anxious patients are at very high risk of a mood and/or anxiety disorder themselves. Parental early onset, having 2 affected parents, female gender, and family functioning are important additional markers that can be used in clinical practice to identify those offspring at greatest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 55 publications
3
49
0
4
Order By: Relevance
“…Further inquiry into mechanisms that support children's adaptive regulation within at-risk samples and during significant points in development is warranted (Raver, 2004). In particular, research demonstrates that father involvement may buffer negative effects of risk, including poverty and maternal depression, on children's outcomes (Goodman, Lusby, Thompson, Newport, & Stowe, 2014;Havinga et al, 2017;Mezulis, Hyde, & Clark, 2004). Research also demonstrates significant negative associations between paternal depression and child development (Gentile & Fusco, 2017;Kane & Garber, 2004).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Further inquiry into mechanisms that support children's adaptive regulation within at-risk samples and during significant points in development is warranted (Raver, 2004). In particular, research demonstrates that father involvement may buffer negative effects of risk, including poverty and maternal depression, on children's outcomes (Goodman, Lusby, Thompson, Newport, & Stowe, 2014;Havinga et al, 2017;Mezulis, Hyde, & Clark, 2004). Research also demonstrates significant negative associations between paternal depression and child development (Gentile & Fusco, 2017;Kane & Garber, 2004).…”
Section: Emotion Regulationmentioning
confidence: 99%
“…The effect of PPND on early childhood has been evaluated by researches with longitudinal data from around the world showing emotional and behavioral problems [22], lower social and psychological well-being [23], and internalizing behavior problems [24] in children aged three to 12 years. Furthermore, it has been shown that the risk for offspring mood or anxiety disorders did not differ according to whether the affected parent was the mother or the father, and that children where at significantly greater risk when both parents were depressed [25]. Thus, when considering the consequences that paternal depressive symptoms have on both fathers' and mothers' well-being, as well as on the development children, the accurate and early assessment of PPND is mandatory, although it must be taken into account that, due to the potential stigma related to paternal depression, there is a tendency to postpone the search for help in the affected fathers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to war and violence not only has major consequences for society at large but also has detrimental impact on people's individual lives. Besides trauma-related psychopathology of those exposed, violence and war may also have intergenerational consequences (Betancourt, 2015;Danieli, 1998;Havinga et al, 2017). The term 'transmission' of trauma has been used to describe these consequences, defined as thoughts, feelings, and behaviours generated from the survivors' experiences and transmitted to their offspring (Fonagy, 1999;Kretchmar & Jacobovitz, 2002;Munroe et al, 1995).…”
Section: Introductionmentioning
confidence: 99%